ASSESSING PUBLIC PERCEPTION FOR ILLUMINATION OF BUILDING IN KAYUTANGAN STREET, MALANG, INDONESIA - Baskoro Azis; Herry Santosa; Jenny Ernawati (Institute of Research and Community Outreach, Petra Christian University, Indonesia, 2019)
Malang is well-known for colonial buildings. Visual quality of building in the Kayutangan corridor makes it an icon of Malang City. Assessment of visual quality is affected by daytime and nighttime conditions. Day and night lighting are factors that influenced the visual quality assessment of buildings. This study meant to assess the visual quality of buildings in the kayutangan corridor which has a history and aspects that influence by society during the day and night. This study used a descriptive quantitative method explaining public perception about the visual quality of buildings in Kayutangan street corridors during the day and night. Semantic Differential Scale was the instrument to describe the respondents’ perceptions. From the result showed that visual quality of four of 10 buildings have a low scores and there are six variables that have the most influence on daylight and eight variables at night on buildings in the Kayutangan corridor.